Micro-encapsulation of oat oil using OSA starch with varying crystal structure and particle size: A study on the encapsulation properties and in vitro release behavior - Nuo Wang; Yongqiang Liang; Junjuan Wang; Liang Zou; Xiaoyan Zhao; Dan Wang; Yuanyuan Zhao; Zhiwen Ge; Lizhen Zhang; Peiyou Qin (Agriculture Communications)
This study assessed the effect of octenyl succinic anhydride (OSA)-modified quinoa, rice, maize, potato and pea starches (Q-OSA, R-OSA, M-OSA, Pt-OSA, P-OSA, respectively) with different crystal structures and particle sizes on the morphological, physicochemical, encapsulation and oil release properties of spray-dried oat oil microcapsules. The microcapsules showed an intact particle morphology and successful encapsulation of oat oil by the wall materials. Microcapsules with small granular starch as the wall material formed spherical aggregates after spray drying. OSA modification mainly occurred in the amorphous region of the starch and thus did not change the starch crystal pattern, but it led to a decrease in the relative crystallinity (RC) of the starch. OSA modification enhanced the emulsifying capacity of starch, whereas it decreased their thermal stability (p ​< ​0.05). Q-OSA, with A-type starch and the smallest particle size (1.48 ​μm), showed the highest degree of substitution (DS, 0.0181), the best emulsification properties (EAI, 1.336 ​m2/g), and the greatest encapsulation efficiency (EE, 90.77 %). Conversely, P-OSA, with C-type starch and the second largest particle size (26.63 ​μm), smaller than Pt-OSA (B-type, 41.15 ​μm), exhibited the lowest DS (0.0091) and EE (79.66 %). OSA modification reduced the oil release of microcapsules in the gastric stage, thereby achieving the targeted release of oat oil at the intestinal stage. In particular, Q-OSA was the most effective in protecting oat oil against pepsin and the strong acidic environment. This study provides guidance on the use of OSA-modified small granular starch (e.g. quinoa starch) for encapsulation and delivery systems.